KUALITAS PELAYANAN KELUHAN PELANGGAN DI PT PLN (PERSERO) ULP HASANUDDIN - Armiana, Armiana; Syam, Marniati; Mursakin, Mursakin (LPPM Universitas Muhammadiyah Mamuju, 2024)
This research aims to obtain an overview of the quality of customer complaint service as seen from tangibles (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), and empathy (empathy). The type of research used in this research is qualitative, the types of data are primary data and secondary data. while the informants for this research are managers, Customer Service, data and information management departments and customers of PT PLN ULP Hasanuddin. Meanwhile, the data collection used is observation, interviews and documentation. Meanwhile, the data analysis used is data reduction, data presentation, and drawing conclusions and verification. The results of this research show that the quality of customer complaint service at PT PLN (Persero) ULP Hasanuddin is quite satisfactory in terms of tangible indicators (physical evidence), reliability is not optimal because it does not comply with the time promised by PT PLN in resolving complaints from customers, Responsiveness (responsiveness) in providing services does not serve customer needs quickly so customers feel that PLN P T officers are slow in handling complaints, assurance (guarantee) has not been categorized as good because of complaints from customers who consider officers favoritism to customers they know, and empathy (empathy) in this indicator regarding communication and service information that meets customer desires.